A new soft‐switching high step‐down DC‐DC converter for voltage regular module application. Issue 2 (9th July 2021) - Vesali, Mahmood; Ranjbar, Hosein; Ghafoorian, Farhad
Abstract: This study proposes a high step‐down DC‐DC converter with minimum elements. In the proposed converter, soft switching condition is provided with only one auxiliary switch, which simplifies the structure of the converter. Leakage inductor energy is used to create a zero voltage condition; so the mutations created by this inductor are neutralised. The control of the auxiliary switch is complementary to the main switch, which does not require a new and complex control circuit. Due to low voltage gain, the proposed converter is suitable for use in voltage regulator modules. The proposed converter is completely analysed. To confirm the theoretical analysis, an experimental sample is made and tested at 15 W and the results are presented. Also, the efficiency of the proposed converter at full load is 97.5%.